1991
DOI: 10.1007/bf02041243
|View full text |Cite
|
Sign up to set email alerts
|

The dental amalgam issue. A review

Abstract: Using an interdisciplinary approach, the current position in the dental amalgam controversy and the potential impact of amalgam mercury on human health are reviewed. Aspects of materials science, corrosion, mercury exposure, toxicology, neurology and immunology are included. New data on mercury exposure from corroded amalgam fillings in vivo are presented. The exposure can reach levels considerably over known threshold limit values. Also, measurements of mercury absorption from intraoral air are presented. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…In the rest of the globe amalgam remains popular because it is strong, durable, and relatively inexpensive. It is considered a safe material but despite this concerns over its use remain because of the continuous low-level release of mercury, a substance which is known to be toxic [4–8]. Summaries of some selected research reports concerning amalgam fillings can be found at http://www.yourhealthbase.com/amalgams.html.…”
Section: Dental Amalgammentioning
confidence: 99%
“…In the rest of the globe amalgam remains popular because it is strong, durable, and relatively inexpensive. It is considered a safe material but despite this concerns over its use remain because of the continuous low-level release of mercury, a substance which is known to be toxic [4–8]. Summaries of some selected research reports concerning amalgam fillings can be found at http://www.yourhealthbase.com/amalgams.html.…”
Section: Dental Amalgammentioning
confidence: 99%
“…For several years there has been an intense discussion about possible adverse effects of metals released from dental mercury amalgams (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…A similar survey of dentists found that although 89% of respondents believed that amalgams posed no risk, 52% reported that they would replace such restorations at a patient's request (Gerbert et al 1992). Reviews in both the scientific and lay literature link amalgam restorations to severe psychiatric, neurologic, and immunologic effects (Anonymous 1991;Fung and Molvar 1992;Hanson and Pleva 1991;Weiner et al 1990).…”
mentioning
confidence: 99%